2014
DOI: 10.3109/10408444.2014.910750
|View full text |Cite
|
Sign up to set email alerts
|

Mode-of-action and human relevance framework analysis for rat Leydig cell tumors associated with sulfoxaflor

Abstract: (2014) Mode-of-action and human relevance framework analysis for rat Leydig cell tumors associated with sulfoxaflor, Critical Reviews in Toxicology, 44:sup2, 25-44, DOI: 10.3109/10408444.2014 AbstractSulfoxafl or, a molecule that targets sap-feeding insects, was assessed for carcinogenic potential in groups of 50 Fischer rats fed with diets containing 0, 25, 100, 500 (males), or 750 (females) ppm sulfoxafl or for 2 years according to OECD 453. Sulfoxafl or did not alter the number of rats with Leydig cell tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…While Leydig cell tumours occur frequently in rats and mice, they are diagnosed rarely in humans. This is largely due to quantitative and qualitative species differences in Leydig cell response to hormonal stimuli (Rasoulpour et al, 2014). In rodents, there are several modes of actions for the induction of this tumour by chemical compounds.…”
Section: Testismentioning
confidence: 99%
“…While Leydig cell tumours occur frequently in rats and mice, they are diagnosed rarely in humans. This is largely due to quantitative and qualitative species differences in Leydig cell response to hormonal stimuli (Rasoulpour et al, 2014). In rodents, there are several modes of actions for the induction of this tumour by chemical compounds.…”
Section: Testismentioning
confidence: 99%
“…It has been widely and clinically used. β-HCG is the most important index for treatment of trophocytes and follow-up visits [29, 30] and closely associated with the therapeutic effect. The experimental result has shown that the serum β-HCG decreases significantly after the action of drug, which further demonstrating the role of puerarin in inhibiting the transplanted tumor of the SCID mice with human choriocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies related to the acute and chronic toxic effects of sulfoxaflor on mammalian species. These studies reported that sulfoxaflor may also have carcinogenic [27,28] and teratogenic effects in mammals [29].…”
Section: Introductionmentioning
confidence: 99%